DRIVERS FOR A SUCCESSFUL AND OVERFUNDED REWARD-BASED CROWDFUNDING CAMPAIGN IN THE UNITED KINGDOM - ALVAREZ ARELLANO, Laila Rashida (2018)
Crowdfunding is a novel way to pursue funding within non-professional investors and therefore there is no much literature available about it as of today. This study seek to understand the drivers for success of an overfunded reward-based crowdfunding campaign and a successful crowdfunding campaign in the UK. The results shows that quality is important for a successful and overfunded campaign. Moreover, behaviour of non-professional backers is different from a professional investor, they show friendliness towards others when backing a project. Results also show other possible correlation between drivers which could lead to a higher quality of the project. The project seek to contribute further research such as new regulations for reward crowdfunding, as nowadays there is none.